Cerebral Microbleeds and Macrobleeds: Should They Influence Our Recommendations for Antithrombotic Therapies? - Haley, Kellen E. (2013)
Intracerebral hemorrhage (ICH, or macrobleeds) and cerebral microbleeds—smaller foci of hemosiderin deposits commonly detected by magnetic resonance imaging (MRI) of older adults with or without ICH—are both associated with an increased risk of future ICH. These hemorrhagic pathologies also share risk factors with ischemic thromboembolic conditions that may require antithrombotic therapy, requiring specialists in cardiology, internal medicine and neurology to weigh the benefits versus hemorrhagic risks of antithrombotics in individual patients. This paper will review recent advances in our understanding of hemorrhage prone cerebrovascular pathologies with a particular emphasis on use of these markers in decision making for antithrombotic use.